Extraction of Bovine Serum Albumin by Aqueous Two-Phase System Using PEG4000/Sodium Citrate and PEG8000/Sodium Phosphate - Mahdi, Hawraa A.; Hameed, Khalid W.; A. Ali, Abdul-Jabbar (Al-Khwarizmi Engineering Journal, 2023)
Aqueous Two Phase System (ATPS) or liquid-liquid extraction is used in biotechnology to recover valuable compounds from raw sources. In Aqueous Two-Phase Systems, many factors influence the Partition coefficient, K, (which is the ratio of protein concentration in the top phase to that in the bottom phase) and the Recovery percentage (Rec%). In this research, two systems of ATPS were used: first, polyethylene glycol (PEG) 4000/Sodium citrate (SC), and the second, PEG8000/ Sodium phosphate (SPH), for the extraction of Bovine Serum Albumin (BSA). The behavior of Rec% and K of pure (BSA) in ATPS has been investigated throughout the study by the effects of five parameters: temperature, concentration of polyethylene glycol (PEG4000 and PEG8000), the concentration of Sodium citrate or Sodium phosphate, pH, and the addition of sodium chloride as a supporting agent. The recovery percentage of BSA and its partition coefficient are significantly influenced by these factors to various degrees. The most influential variable in this study is PEG concentration for both systems. In addition to the PEG concentration, the stabilizing impact of NaCl is a crucial factor. The interaction between biomolecules and PEG gets more hydrophobic as the PEG concentration is raised. In the first system (PEG4000/SC), the maximum recovery percentage and partition coefficient were 98.99% and 97.69, respectively, at 31°C, PEG4000 concentration 1.5g/10 ml, Sodium citrate concentration 2.7 g/10 ml, pH 10, and 0.5 M NaCl concentration. While in the second system (PEG8000/SPH), the maximum recovery percentage and partition coefficient was 98.93% and 92.12, respectively, at 31oC, PEG8000 concentration 1.5 g/10 ml, Sodium phosphate concentration 2.4 g/10 ml, pH 10, and concentration of NaCl 0.5 M.